Age of the subducting Pacific slab beneath East Asia and its geodynamic implications - Liu, Xin; Zhao, Dapeng; Li, Sanzhong; Wei, Wei (Earth and planetary science letters, 2017)
We study the age of the subducting Pacific slab beneath East Asia using a high-resolution model of P-wave tomography and paleo-age data of ancient seafloor. Our results show that the lithosphere age of the subducting slab becomes younger from the Japan Trench (∼130 Ma) to the slab's western edge (∼90 Ma) beneath East China, and the flat (stagnant) slab in the mantle transition zone (MTZ) is the subducted Pacific plate rather than the proposed Izanagi plate which should have already collapsed into the lower mantle. The flat Pacific slab has been in the MTZ for no more than ∼10–20 million years, considerably less than the age of the big mantle wedge beneath East Asia (>110 million years). Hence, the present flat Pacific slab in the MTZ has contributed to the Cenozoic destruction of the East Asian continental lithosphere with extensive intraplate volcanism and back-arc spreading, whereas the destruction of the North China Craton during the Early Cretaceous (∼140–110 Ma) was caused by the subduction of the Izanagi (or the Paleo-Pacific) plate. •Age distribution of the subducting Pacific slab beneath East Asia is estimated.•The current flat slab in the MTZ beneath East Asia is the subducting Pacific plate.•The big mantle wedge has existed much longer than any slabs in the MTZ.